2014
DOI: 10.1016/j.aju.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The management of genitourinary fistula in the third millennium

Abstract: BackgroundA vesicovaginal fistula (VVF) is an abnormal fistulous tract between the bladder and vagina, causing continuous loss of urine via the vagina. VVF is a relatively uncommon condition, but there is a drastically higher prevalence in the developing world. Furthermore, iatrogenic postoperative VVF is most common in developed countries, compared to mainly obstetric trauma in developing countries. In this review we focus on the development of current management techniques for VVF.MethodsMedline was searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 52 publications
2
83
0
11
Order By: Relevance
“…It has been reported that clinical presentation of UVF is subtly different from VVF. Intermittent or position‐related vaginal leakage of urine can be expected with UVF, whereas urine leakage is more constant with pure VVF . In the present cohort, the UVFs were associated with concurrent VVF, which made the clinical picture mixed in nature.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It has been reported that clinical presentation of UVF is subtly different from VVF. Intermittent or position‐related vaginal leakage of urine can be expected with UVF, whereas urine leakage is more constant with pure VVF . In the present cohort, the UVFs were associated with concurrent VVF, which made the clinical picture mixed in nature.…”
Section: Discussionmentioning
confidence: 59%
“…Other clinical signs of UVF are ileus and abdominal pain consequent to intraperitoneal leak of urine, recurrent ascending urinary tract infections, and renal impairment. Additional clinical signs of VVF can include vulvar irritation and excoriation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicovaginal fistula (VVF) is a direct communication between the bladder and vagina. In high‐income countries, VVF is associated with malignancy, radiation, and pelvic surgery . Classical VVF presentation includes urinary leakage from the vagina, vulvovaginal irritation, and recurrent infections.…”
Section: Suture Materials Usedmentioning
confidence: 99%
“…The lowest incidence is with transvaginal (0.2:1000) followed by transabdominal (1:1000), and laparoscopic procedures (2.2:1000). 2 Over the last 200 years, multiple repair techniques for VVF have been used. Urologists have utilized abdominal, laparoscopic, and robotic approaches for repair of complex fistulas; these approaches are technically difficult.…”
Section: Introductionmentioning
confidence: 99%